Research on the Application of Digital Technology in University Procurement Auditing - Ning, Yi-Zi (European Journal of Applied Sciences, 2024)
Digital technology is applied in the audit of procurement in universities to identify potential risks and issues, improve audit efficiency, and save manpower and time costs. The application of this technology can enhance risk management, strengthen supervision and management of procurement activities, and support decision improvement. Intuitive and clear audit reports and visualized analysis results provide decision support for university management, accurately assess risks, and formulate improvement measures. University procurement audits can comprehensively and accurately analyze procurement data, identify potential problems and risks, and provide stronger technical support for university procurement management.